ROUND CHARACTER DEVELOPMENT OF ELIO IN ELIO (2025): A STUDY BASED ON FORSTER AND MASLOW - Surya, Annisa Keyshawardhana; Zein, Ratu Azizah Arzellya; Rosalinah, Yanti (Elite : English and Literature Journal, 2025)
Literary works serve as a medium for expressing human thoughts, emotions, and experiences, and films are one of the most dynamic forms of such expression. The film Elio (2025) portrays the psychological and emotional journey of its main character, Elio, whose development reflects the process of achieving self-actualization. This study aims to analyze Elio’s character development as a round character through E.M. Forster’s theory of characterization and to explore his psychological transformation using Abraham Maslow’s hierarchy of needs theory. Employing a psycho-literary approach, this research integrates literary and psychological perspectives to examine how Elio’s evolving behavior and mindset represent the fulfillment of human needs, from safety and belongingness to self-awareness and actualization. The findings reveal that Elio’s transformation embodies the characteristics of a round character and aligns with the progressive stages of Maslow’s hierarchy. The study concludes that Elio illustrates how film narratives can serve as a reflection of human psychological growth and the pursuit of self-discovery.